2008
DOI: 10.1103/physrevc.77.051304
|View full text |Cite
|
Sign up to set email alerts
|

Absence of low-temperature dependence of the decay ofBe7andAu198

Abstract: Absence of low-temperature dependence of the decay of 7 Be and 198 Au in metallic hosts

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…While the original measurement by Spillane et al [4] followed the decay for only a little over one half-life, we recorded the decay with much better statistics for over ten half-lives at both room temperature and at 19 K. Our results showed the half-lives at the two temperatures to be the same within 0.04%, a limit two orders of magnitude less than the difference claimed by Spillane et al This null result was subsequently confirmed by two other measurements of 198 Au, which set limits of 0.13% in a Al-Au alloy host [10] and 0.03% in gold [11]. The latter reference also reported a new 22 Na decay measurement, which set an upper limit on the temperature dependence of that β + decay at 0.04%, again nearly two orders of magnitude below the earlier claim, in this case by Limata et al [5].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…While the original measurement by Spillane et al [4] followed the decay for only a little over one half-life, we recorded the decay with much better statistics for over ten half-lives at both room temperature and at 19 K. Our results showed the half-lives at the two temperatures to be the same within 0.04%, a limit two orders of magnitude less than the difference claimed by Spillane et al This null result was subsequently confirmed by two other measurements of 198 Au, which set limits of 0.13% in a Al-Au alloy host [10] and 0.03% in gold [11]. The latter reference also reported a new 22 Na decay measurement, which set an upper limit on the temperature dependence of that β + decay at 0.04%, again nearly two orders of magnitude below the earlier claim, in this case by Limata et al [5].…”
Section: Introductionsupporting
confidence: 66%
“…The status of electron-capture decay is also less definitive. One new measurement of 7 Be decay in copper [10] found no temperature dependence greater than 0.3% but another [14] actually found a small change in half-life-0.22(8)%-depending on whether the host material was a conductor (Cu or Al) or an insulator (Al 2 O 3 or PVC), both at room temperature. In neither case is the result as precise as has been achieved for β − and β + decays.…”
Section: Introductionmentioning
confidence: 99%
“…In summary we confirm the conclusion of recent works [2,3,4,5] that no temperature effect on the half-life of 198 Au is present within the statistical uncertainties of this experiment. Table 1.…”
supporting
confidence: 92%
“…Note that electron capture decay rates may depend on the material hosting the radioactive isotope via small modifications of the electron density around the EC-decaying nucleus (see, e.g., [8] and references therein). In contrast to the above results, several experiments carried out at a later stage on the β-decaying isotopes 198 Au [9][10][11][12], 22 Na [11,12], 64 Cu [13], and 74 As [14], and on the EC-decaying 7 Be [10], did not observe any changes of the half-lives up to the permille level when these isotopes were embedded in a metallic environment and cooled down to 10-20 K.…”
Section: Introductionmentioning
confidence: 53%
“…These dedicated half-life measurements bring down the level to which no temperature and host-material effect is observed on nuclear half-lives for α decays to the same level of precision as was already established for β decays and EC decays in Refs. [8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%